Eco-friendly ZIF-67/rice straw-derived cellulose acetate electrospun nanofiber mats for efficient CO2 capturing and selectivity removal of methyl orange dye. Issue 6 (December 2022) - Mo, Jieqiong; Hu, Die; Liu, Xin; Sun, Ya; Li, Xiaofang; Wang, Chunlei; Chai, Bo; Ding, Deng; Yan, Juntao; Sun, Linbing
Abstract: Electrospun nanofiber membranes are ubiquitous in the ecological environment due to the high specific surface area and porosity, excellent functionality and recycling. Surface enriched ZIF-67 that incorporated into electrospun rice straw-derived cellulose acetate (RSCA) nanofibers mats were synthesized using a facile in-situ growth strategy. The RSCA was achieved by the acetylation reaction of rice straw-derived cellulose, which was extracted from the recycled waste agricultural rice straw by green solvent. The structures and properties of ZIF-67/RSCA were investigated to reveal the mechanism of in-situ growth method. ZIF-67/RSCA mat shows efficient CO2 capture and water treatment performance. The achieved ZIF-67/RSCA-0.1 M nanofiber membrane possesses optimal capacities for CO2 (1.33 mmol/g at 273 K and 101 kPa), which reached to 70% of ZIF-67 powders. MO adsorption capacity of ZIF-67/RSCA-0.1 M membrane was matched with the pseudo-second-order kinetic model, and their equilibrium adsorption capacity towards MO was found to be 11.20 mg/g at room temperature, which is about 15 times as that of pure RSCA nanofibers membrane (0.77 mg/g). Moreover, the ZIF-67/RSCA could selectively adsorb the MO, while it cannot remove the MB pollutant. The detailed analysis of BET and Zeta potential indicated that larger specific surface area and positive potential of ZIF-67/RSCA were favorable for efficient adsorption and selectivity. We believe the approach to fabricate ZIF-67/RSCA nanofibers membrane using the rice straw for removing CO2 and MO is a win-win strategy for the application of agricultural waste to environmental pollution. Graphical Abstract: ga1 Highlights: The recycled waste agricultural rice straw is used to obtain the RSCA by a method of green solvent. ZIF-67/RSCA membranes are synthesized by in-situ growth method and the mechanism of growth are investigated in detail. ZIF-67/RSCA mats show efficient CO2 capture and selectively adsorb MO of mixed organic dyes solution quickly. The efficient and selectivity adsorption of composite are ascribed to high surface area and electrostatic attraction.